Moments Analysis in Risk and Performance Monitoring of Funds of Hedge Funds - LEE, David K. C. (Institutional Knowledge at Singapore Management University, 2006)
This chapter introduces a practical approach to monitoring the risk and performance of funds of hedge funds from the viewpoints of U.S. and global equity investors. It focuses on the impacts when we include funds of hedge funds into investors' portfolios and examines whether the inclusion helps to insulate the overall portfolio when the market is down, to capture the upside, and to reduce portfolio volatility under different market conditions. An advantage of this approach is that it alleviates the problems that can arise if hedge fund returns are skewed and leptokurtic and nonlinearly related to market returns. The results also show that very few of the funds provide downside protection, upside capture, and reduced volatility on the downside. It demonstrates that there is an implicit trade-off between funds of hedge funds returns and our risk measures, which is an interesting question for future research. The proposed methodology can be applied to other classes of hedge funds and even other types of assets when investors exhibit similar specified preferences and where returns exhibit differing relations to held portfolios in up and down markets.